The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1073/pnas.1603282113
|View full text |Cite
|
Sign up to set email alerts
|

Control of serotonin transporter phosphorylation by conformational state

Abstract: Serotonin transporter (SERT) is responsible for reuptake and recycling of 5-hydroxytryptamine (5-HT; serotonin) after its exocytotic release during neurotransmission. Mutations in human SERT are associated with psychiatric disorders and autism. Some of these mutations affect the regulation of SERT activity by cGMPdependent phosphorylation. Here we provide direct evidence that this phosphorylation occurs at Thr276, predicted to lie near the cytoplasmic end of transmembrane helix 5 (TM5). Using membranes from He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Computational modeling predicts that the conformational equilibrium of DAT is shifted towards occluded-intermediate (OC) and IF states in the presence of substrates ( Cheng and Bahar, 2015 ). This prediction is supported by the experimental evidence in studies of SERT ( Zhang et al, 2016 ). We found that oligomerization and endocytosis of DAT in AIM-100-treated cells were significantly decreased by saturating concentrations (20–100 µM) of DAT substrates, dopamine (DA) and amphetamine (Amph) ( Figure 6 ).…”
Section: Resultssupporting
confidence: 67%
“…Computational modeling predicts that the conformational equilibrium of DAT is shifted towards occluded-intermediate (OC) and IF states in the presence of substrates ( Cheng and Bahar, 2015 ). This prediction is supported by the experimental evidence in studies of SERT ( Zhang et al, 2016 ). We found that oligomerization and endocytosis of DAT in AIM-100-treated cells were significantly decreased by saturating concentrations (20–100 µM) of DAT substrates, dopamine (DA) and amphetamine (Amph) ( Figure 6 ).…”
Section: Resultssupporting
confidence: 67%
“…To facilitate 5HT reuptake, the transporter needs to undergo distinct conformational changes. In principle, these changes expose the substrate binding site(s) to one side of the membrane at a time, according to the so-called alternatingaccess mechanism [9], support for which has been provided by structural modeling and biochemical experiments [10][11][12], and recently also by X-ray and cryo-EM crystallography [13][14][15]. Taken together, the hSERT transport cycle can be represented roughly as shown in Fig 1, albeit with the caveat that several important details remain elusive.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast, serotonin, in the presence of its symported ions Na ϩ and Cl Ϫ , enhanced accessibility at these positions, consistent with this region contributing to the substrate permeation pathway. Notably, there is strong evidence for regulation of SERT function through phosphorylation of Thr-276 (30), which aligns with Gly-171 in MhsT, adjacent to unwound Arg-174 -Met-180 in MhsT U . In the outward-facing SERT structure, this residue is located on the back side of the helical TM5i-IL2 region with its side chain forming an H-bond with the backbone of Ser-269 (13), in a position and orientation that would seem rather inaccessible to kinases.…”
Section: The Role Of Tm5 In Na2 Release and Inward Openingmentioning
confidence: 99%